Carbon performance and carbon emissions disclosure: Are they in sync and harmony? - Handono, Wiyasto Dwi; Purnamasari, Dian Indri; Kusharyanti, Kusharyanti (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
Carbon emission disclosure has emerged as a critical aspect of environmental disclosure in both international and national contexts. This research examines the impact of carbon performance on carbon emission disclosure in the Indonesian energy sector, utilizing data from companies listed on the Indonesian Stock Exchange. The analysis using Ordinary Least Squares (OLS) regression and robustness checks indicates that both direct (Scope 1) and indirect (Scope 2) emissions negatively affect carbon emission disclosure. This research underscores that low direct and indirect emissions motivate companies to enhance transparency in their carbon reporting practices. The research provides empirical evidence from emerging markets, indicating that firms are encouraged to adopt renewable energy solutions to achieve low-carbon performance. Furthermore, this study contributes to the growing body of research on environmental accounting and offers valuable insights for policymakers and carbon emission professionals seeking to enhance corporate sustainability reporting frameworks. Such insights are crucial for promoting greater transparency and accountability in corporate environmental disclosures